Neck tongue syndrome: operative management. Issue 4 (April 1984) - Elisevich, K; Stratford, J; Bray, G; Finlayson, M
Abstract : A 53-year-old woman with assimilation of the atlas to the occiput presented with paraesthesiae in the right half of her tongue and ipsilateral neck pain aggravated by head turning. After being intermittent for several years, the symptoms eventually became persistent and increasingly incapacitating. At operation, the C2 spinal nerves were found to be compressed by protuberant atlanto-axial joints, particularly on the right side. The superficial parts of the resected C2 spinal nerves showed a loss of both myelinated and unmyelinated nerve fibres. After operation, the patient experienced partial relief of her symptoms.